Analisis Manajemen Gudang di PT XYZ Cabang Bandung-Leuwigajah - Febriani, Devita Aviva; Yun, Yun (Universitas Batanghari Jambi, 2025)
This study aims to analyze the implementation of WMS at PT XYZ Branch Bandung-Leuwigajah, a large distribution company in Indonesia, focusing on issues such as discrepancies between system data and physical stock, difficulties in recording product returns, and wasted time in manual stocktaking processes. The research employs a qualitative approach, using Root Cause Analysis (RCA) and semi-structured interviews with relevant personnel at the company. The results indicate that the implementation of WMS can reduce errors in stock management and improve operational efficiency, particularly in stocktaking and product return management. Furthermore, the study also identifies challenges in integrating the system with diverse product characteristics and the need for further training to maximize the use of WMS.